Relationship of Medication Adherence to Clinical Outcome in Patients Type 2 Diabetes with Modified Morisky Adherence Scale 8 (MMAS 8) - Niken Luthfiyanti; Ardi Setyawan; Kharisma Jayak Pratama (Lembaga Pengembangan Kinerja Dosen, 2024)
Diabetes melitus is a chronic condition desease that requires continued use of medication. High adherence to treatment will produce good clinical results and play a role in improving the quality of life of diabetes melitus sufferers. The following research aims to assess the relationship between adherence to medication use and clinical outcomes for patients with type 2 diabetes mellitus at RSUD DR. Moewardi Surakarta which was conducted in the period April – June 2024. This research used a cross sectional method with a total of 98 patients as respondents who met the inclusion and exclusion criteria. Adherence data was assessed using the Modified Morisky Adherence Scale 8 (MMAS 8) questionnaire, and clinical outcomes were assessed from fasting or fasting blood glucose values ​​and %HbA1C from medical record data. Analysis of the relationship between adherence and clinical outcomes using chi-square. The results of the level of treatment compliance can be divided into 3 categories, namely: high treatment compliance has a percentage of 24.5%, moderate treatment compliance has a percentage of 46.9%, and low treatment compliance has a percentage of 28.6%. Clinical outcomes were achieved by 38.8% and not achieved by 62.2%. There is a relationship between adherence medication and therapeutic outcomes in type 2 diabetes melitus patients with a Pearson chi square value of 0.011. Based on these data, pharmacist professionals need to place greater emphasis on adherence with medication use in type 2 diabetes mellitus patients to obtain good clinical outcomes.